2011
DOI: 10.1088/0067-0049/197/2/35
|View full text |Cite
|
Sign up to set email alerts
|

Candels: The Cosmic Assembly Near-Infrared Deep Extragalactic Legacy Survey

Abstract: The Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS) is designed to document the first third of galactic evolution, over the approximate redshift (z) range 8-1.5. It will image >250,000 distant galaxies using three separate cameras on the Hubble Space Telescope, from the mid-ultraviolet to the near-infrared, and will find and measure Type Ia supernovae at z > 1.5 to test their accuracy as standardizable candles for cosmology. Five premier multi-wavelength sky regions are selected, each … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
1,636
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,901 publications
(1,677 citation statements)
references
References 217 publications
11
1,636
0
2
Order By: Relevance
“…In order to obtain multiwavelength photometry for these galaxies, we cross-matched this sample with the public Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS; Grogin et al 2011;Koekemoer et al 2011) catalog for the Great Observatory Origins Deep Survey South field (GOODS-S) obtained by Guo et al (2013). This catalog contains photometry in 17 broadbands, from 0.37 through 8.0 μm, obtained with ground-and space-based telescopes, including HST and Spitzer (Ashby et al 2015).…”
Section: Samplementioning
confidence: 99%
“…In order to obtain multiwavelength photometry for these galaxies, we cross-matched this sample with the public Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS; Grogin et al 2011;Koekemoer et al 2011) catalog for the Great Observatory Origins Deep Survey South field (GOODS-S) obtained by Guo et al (2013). This catalog contains photometry in 17 broadbands, from 0.37 through 8.0 μm, obtained with ground-and space-based telescopes, including HST and Spitzer (Ashby et al 2015).…”
Section: Samplementioning
confidence: 99%
“…For consistency, the depth shown is the 5σ limiting flux for point sources, excluding confusion noise ( as described in Section 4.2), calculated from the Spitzer performance estimation tool (http://ssc.spitzer.caltech.edu/ warmmission/propkit/pet/senspet /index.html) in each case. The surveys are (from left to right): GOODS, the Spitzer follow-up to the CANDELS HST survey (Cosmic Assembly Near-IR Deep Extragalactic Legacy Survey, Grogin et al 2011), the Spitzer Extragalactic Deep Survey (SEDS, Program identifier-hereafter PID-60022, 61040, 61041, 61042, 61043, P.I. G. Fazio), the Spitzer IRAC/MUSYC Public Legacy in E-CDFS (SIMPLE) survey (Spitzer, PID 20708), the Spitzer Ultra Deep Survey (SpUDS, PID 40021, P.I.…”
Section: Selection Of Fieldsmentioning
confidence: 99%
“…Progress in extragalactic astronomy has been greatly enhanced by deep surveys such as the Great Observatories Origins Deep Survey (GOODS; Dickinson et al 2003), the Cosmic Evolution Survey (COSMOS; Sanders et al 2007), the Galaxy Mass Assembly Ultradeep Spectroscopic Survey (GMASS; Cimatti et al 2008), and the HST Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS; Grogin et al 2011;Koekemoer et al 2011), which have allowed us to study the evolution of galaxies from the earliest cosmic epochs. However, a limitation of such surveys is the relatively small volumes probed, even at high redshifts: for example, Ilbert et al (2006) find noticeable field-to-field variations in redshift distributions in the Canada-France-Hawaii Telescope Legacy Survey (CFHTLS 43 ) in fields of 0:7-0:9 deg 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Grogin et al 2005). The SEDS fields are also covered by CANDELS (Cosmic Assembly Near-Infrared Deep Extragalactic Legacy Survey; Grogin et al 2011), which has obtained deep, highresolution HST imaging at 1 to 1.6 microns with HST WFC3 in portions of these fields. Recent CANDELS results have found that, for X-ray selected AGN, the fraction of irregular and disturbed host galaxies is no greater than that of a control sample (Kocevski et al 2012).…”
Section: Mid-ir Variability Surveys For Agnmentioning
confidence: 99%